Challenges and advances in waterless cosmetic product development – raising awareness of water sustainability - Lukić, Milica; Krajišnik, Danina (Archives of Pharmacy, 2024)
Water conservation is an essential strategy for managing the world's limited water resources. The life cycle of cosmetic products, which are used in immeasurable quantities in everyday life, involves significant water consumption. Water is a common ingredient in cosmetic products, and it is also used in the manufacturing process. Numerous strategies are being developed to reduce water consumption in the life cycles of different cosmetic products. This paper therefore focuses on efforts to minimize water use in formulation development and challenges which accompany these efforts. Waterless cosmetic products are a trend that started with less motivation for sustainability, but combined with the global awareness of environmental benefits, it has become an attractive formulation strategy for water sustainability. Waterless cosmetic formulations reduce direct water footprint by not using water as a main ingredient in the formulations. Nevertheless, designing waterless cosmetics is a great challenge. This paper summarizes the tendencies, principles and key considerations of formulation, as well as the benefits and advantages of waterless cosmetic products. It points out the importance of reducing both the water and carbon footprint of cosmetic products, and consequently the contribution cosmetics can make to quality of life and sustainable development.
Keywords: topical formulations; cosmetic products design; waterless products; water sustainability